Construction Delays Analysis in the Kampung Akuarium Flats Project, Penjaringan-Jakarta - Amalia, Intan Dian; Sudjatmiko, Eddy Triyanto; Bangkara, Anaconda (President University, 2023)
The most common impediment to project work is a delay in implementing work activities. Even though the completion time has been calculated, there are several influencing factors, such as natural factors that cannot be predicted, late material delivery, a lack of workers that are not optimal when doing project work, and insufficient funds. In this case, the construction project of the Kampung Akuarium flats in Penjaringan area of North Jakarta was delayed from both technical and non-technical. The objective of this studyÂ isÂ to identify the factors causing the project delays and the delay time of the project. This research was conducted by collecting data obtained and processed using Microsoft Project 2019 and the Critical Path Method (CPM) to help identify the problems. From the results that have been analyzed, critical paths include the structural work, finishing architecture 3rd floor, finishing architecture 4th floor, and finishing architecture 5th floor. If not completed immediately or delayed during implementation, the entire project schedule will be delayed. This has an effect where the initial contract plan was completed in 182 days to 259 days with a difference of 77 days or 11 weeks.